'There's more to life than money and health': Family caregivers' views on the role of Power of Attorney in proxy decisions about research participation for people living with dementia. (January 2021) - Shepherd, Victoria; Griffith, Richard; Hood, Kerenza; Sheehan, Mark; Wood, Fiona
People living with dementia may experience difficulties when making decisions for themselves in the later stages of the condition. While there are mechanisms in England and Wales for appointing an attorney to make decisions about welfare and finances on their behalf, there are no provisions for appointing an attorney to make future decisions about research participation. This is despite a growing focus on Advanced Care Planning and other processes that provide opportunities to discuss future preferences and ensure that decisions are made in line with those preferences. This qualitative study with 15 family caregivers who had acted as research proxies explored the role of Power of Attorney in their decisions about research, and their views about extending current legal arrangements to include research. Five themes were identified: the holistic nature of decision-making; the 'power' of attorney; making decisions by putting yourself in their shoes; support for bringing research under the umbrella of attorney arrangements and a unifying theme of trusting relationships. Legal provisions for prospectively appointing a research proxy may encourage discussion about future wishes and so enable decisions about research to be made that are in accordance with the person's preferences and wishes. However, further consultation with the public including people living with dementia and their families, and a range of stakeholders is needed. Providing guidance to families, people living with dementia and the wider research community may provide greater clarity and improve decision-making in the meantime.